Work-Family Conflict among Women: An Islamic Perspective (Indonesian Journal of Counseling and Development, 2023)
Work-family conflict is a form of role conflict that arises within an individual due to conflicting pressures from work and family roles. This research focuses on work-family conflict as experienced by women. The aim of this study is to understand how work-family conflict is experienced by female educators. This study employs a descriptive quantitative research method, utilizing a work-family conflict scale. The sampling technique used was a saturated sample, comprising 21 female educators. The results indicate that the work-family conflict experienced by female educators falls into the high category. This suggests that they have not yet mastered the management or regulation of their roles, both within the family and at work.